Mechanisms of Drug Resistance in Cancer: The Role of Extracellular Vesicles. Issue 23 (25th October 2017) - Samuel, Priya; Fabbri, Muller; Carter, David Raul Francisco
Abstract: Drug resistance remains a major barrier to the successful treatment of cancer. The mechanisms by which therapeutic resistance arises are multifactorial. Recent evidence has shown that extracellular vesicles (EVs) play a role in mediating drug resistance. EVs are small vesicles carrying a variety of macromolecular cargo released by cells into the extracellular space and can be taken up into recipient cells, resulting in transfer of cellular material. EVs can mediate drug resistance by several mechanisms. They can serve as a pathway for sequestration of cytotoxic drugs, reducing the effective concentration at target sites. They can act as decoys carrying membrane proteins and capturing monoclonal antibodies intended to target receptors at the cell surface. EVs from resistant tumor cells can deliver mRNA, miRNA, long noncoding RNA, and protein inducing resistance in sensitive cells. This provides a new model for how resistance that arises can then spread through a heterogeneous tumor. EVs also mediate cross‐talk between cancer cells and stromal cells in the tumor microenvironment, leading to tumor progression and acquisition of therapeutic resistance. In this review, we will describe what is known about how EVs can induce drug resistance, and discuss the ways in which EVs could be used as therapeutic targets or diagnostic markers for managing cancer treatment. While further characterization of the vesiculome and the mechanisms of EV function are still required, EVs offer an exciting opportunity in the fight against cancer.